Effects of aloe emodin on U87MG glioblastoma cell growth: In vitro and in vivo study. Issue 11 (15th September 2018) - Arcella, Antonietta; Oliva, Maria Antonietta; Staffieri, Sabrina; Sanchez, Massimo; Madonna, Michele; Riozzi, Barbara; Esposito, Vincenzo; Giangaspero, Felice; Frati, Luigi
Abstract: Glioblastoma, the most aggressive and malignant form of glioma, appears to be resistant to various chemotherapeutic agents. Hence other approaches have been investigated to target more pathways involved in glioblastoma development and progression. Here we investigate the anticancer effect of Aloe‐Emodin (AE), an anthraquinone compound presents in the leaves of Aloe arborescens, on human glioblastoma cell line U87MG. U87MG were treated with various concentrations of AE (20 and 40 μM) for different times (24, 48, and 72 hr). Cell growth was monitored by daily cell count after treatments. Growth analysis showed that AE significantly decrease proliferation of U87MG in a time and dose dependent manner. FACS analysis demonstrates a block of cell cycle in S and G2/M phase. AE probably induced also apoptosis by releasing of apoptosis‐inducing factor: PARP and Lamin activation leading to nuclear shrinkage. In addition, exposure of U87MG to AE reduced pAKT phosphorylation. AE inhibition of U87MG growth is a result of more mechanism together. Here we report that AE has a specific growth inhibition on U87MG also in in vivo. The growth of U87MG, subcutaneously injected in nude mice with severe combined immunodeficiency, is inhibited without any appreciable toxic effects on the animals after AE treatment. AE might represent a conceptually new lead antitumor adjuvant drug.